The Effect of Competence, Training, and Career Development on the Performance of XYZ Junior High School Teachers in Bekasi City - David, David; Cornellius, Josephin; Iqbal, Widy Maulana; Tyas, Ari Anggarani Winadi Prasetyoning (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study investigates the impact of competence, training, and career development on the performance of teachers at SMP XYZ in Bekasi City. A quantitative research approach was employed using a survey method, with data collected through questionnaires distributed to 30 teachers. The sampling technique applied was the saturated sample method, ensuring all teachers participated as respondents. Instrument validity and reliability tests confirmed that all questionnaire items were both valid and reliable for analysis. Data were analyzed using multiple linear regression to determine the relationship between the independent variables (competence, training, and career development) and the dependent variable (teacher performance). The results revealed that competence has a positive and significant effect on teacher performance, indicating that higher levels of teacher competence contribute directly to improved performance. However, training and career development did not show statistically significant effects on teacher performance. The Adjusted R Square value of 0.547 indicates that 54.7% of the variance in teacher performance can be explained by the three independent variables, while the remaining 45.3% is influenced by other factors not included in this study. These findings emphasize the critical role of teacher competence in enhancing educational outcomes and suggest that schools should prioritize competence development to improve teacher performance effectively.